Impact of Talent Management Strategies on Organizational Performance in Selected Deposit Money Banks in Lagos State, Nigeria - Agbaeze, Kalu Emmanuel; Monyei, Ezieshi Francis; Agu, Okoro Aguc (International Research Journal of Management, IT & Social Sciences, 2017)
This study critically examined the Impact of Talent Management Strategies on Organizational Performance in Selected Deposit Money Banks (DMB) in Lagos State, Nigeria. Specifically, the study sought to; (i) determine the extent succession planning relates to sustainability; (ii) ascertain to what extent human capital development impacts on innovative capabilities of employees; and, (iii) examine the degree compensation impacts on employee engagement, in selected DMBs under study. The study adopted the survey design. The population of the study was 3126 comprising management and junior staff drawn from the selected DMBs in Lagos state, Nigeria. These include First Bank of Nigeria Plc, United Bank for Africa Plc, Zenith Bank Plc, Access Bank Plc, and Ecobank Plc. The sample size of 359 was obtained from the population using Bill Goddenâs formula at 5% error margin and 90% level of confidence...